Criteria Used for the Diagnosis of Myofascial Trigger Points in Clinical Trials on Physical Therapy: Updated Systematic Review. Issue 12 (December 2020) - Li, Lihui; Stoop, Rahel; Clijsen, Ron; Hohenauer, Erich; Fernández-de-las-Peñas, César; Huang, Qiangmin; Barbero, Marco
Abstract : Objective: The objective of this study was to conduct an updated systematic review of diagnostic criteria for myofascial trigger points (MTrPs) used in clinical trials of physical therapy interventions from 2007 to 2019. Methods: MEDLINE and Physiotherapy Evidence Database (PEDro) were searched using the following MeSH keywords: "trigger points, " "trigger point, " "myofascial trigger point, " "myofascial trigger points, " "myofascial pain, " and "myofascial pain syndrome." The MeSH keywords were combined by using Boolean operators "OR"/"AND." All physiotherapy clinical trials including patients with musculoskeletal conditions characterized by at least 1 active MTrP or latent MTrP in any body area were selected. We pooled data from an individual criterion and criteria combinations used to diagnose MTrPs. The protocol was developed in accordance with the PRISMA-P guidelines. Results: Of 478 possibly relevant publications, 198 met the inclusion criteria. Of these 198 studies, 129 studies (65.1%) stated specifically the diagnostic criteria used for MTrPs in the main text, 56 studies (28.3%) failed to report any method whereby MTrP was diagnosed, and 13 studies (6.6%) adopted expert-based definitions for MTrPs without specification. Of 129 studies, the 6 criteria applied most commonly were: "spot tenderness" (n=125, 96.9%), "referred pain" (95, 73.6%), "local twitch response" (63, 48.8%), pain recognition (59, 45.7%), limited range of motion" (29, 22.5%), and "jump sign" (10, 7.8%). Twenty-three combinations of diagnostic criteria were identified. The most frequently used combination was "spot tenderness, " "referred pain, " and "local twitch response" (n=28 studies, 22%). Conclusions: A number of the included studies failed in properly reporting the MTrP diagnostic criteria. Moreover, high variability in the use of MTrP diagnostic was also observed. Spot tenderness, referred pain, and local twitch response were the 3 most popular criteria (and the most frequently used combination). A lack of transparency in the reporting of MTrP diagnostic criteria is present in the literature. Registry: This systematic review was registered under the Centre for Reviews and Dissemination, PROSPERO number: CRD42018087420. Abstract : Supplemental Digital Content is available in the text.